TRAJECTORY OF TECHNICAL EDUCATION IN BRAZIL: HISTORICAL ASPECTS (Fiep Bulletin - online, 2025)
Introduction: Technical education in Brazil plays a strategic role in training a qualified workforce, which is essential for the country's socioeconomic development. However, its trajectory is marked by challenges related to consolidating public policies and overcoming regional inequalities. Objective: To investigate the institutional milestones, legislative transformations, and challenges encountered in Brazil's historical trajectory of technical education. Methods: The study employed a qualitative approach based on the documental analysis of relevant legislative and academic sources. The selection of documents followed criteria of historical relevance, and the data were organized and interpreted into thematic categories. Results: The results highlighted the main institutional milestones and legislative transformations that shaped technical education in Brazil and the challenges faced throughout its historical trajectory. Conclusion: The conclusion emphasizes the importance of technical education as a driver of socioeconomic development, highlighting its strategic role in social inclusion and the training of a qualified workforce.
Keywords: Technical education; socioeconomic development; legislation